Research on Information Sciences in Cuba: Flows of knowledge during the period 2005-2019 - Vega-Almeida, Rosa Lidia; Arencibia-Jorge, Ricardo (Iberoamerican Journal of Science Measurement and Communication, 2021)
Objective. To characterize the Cuban research on Information Sciences, and to analyze the flows of knowledge between its intellectual base and the research fronts influenced by Cuban researchers. Design/Methodology/Approach. The subject category “Information Science and Library Science” from Web of Science, during the period 2005-2019, was studied. The intellectual base was determined by author co-citation analysis. Citing articles of Cuban authors were analyzed by bibliographic coupling and term co-occurrence techniques. A documental analysis of bibliometric studies on the discipline in Cuba was developed. Results/Discussion. The diversification of the topics discussed overtime was verified, which have been in correspondence with social needs. A sustained increase in scientific production was observed, based on collaboration and intense postgraduate training. A greater number of journals were used to disseminate the results, which were cited from multiple knowledge areas. Conclusions. The communicating vessels between the intellectual base and influenced research fronts evidenced the appropriation of foreign and Cuban referents in the disciplinary constructive process, their growing influence on the global scientific community, and the configuration of a cognitive space of disciplinary confluence between Library Science, Information Science, Archival Science, and Social Communication, closely connected with the thematic axes that lead global research. Originality/Value. An exhaustive documentary review, combined with bibliometric techniques, allowed the thematic characterization and analysis of the evolution of Cuban informational thinking during the last 15 years (2005-2019), in relation to its regional and global context.